A Financial Ratio and Non-parametric Analysis of Malaysian Banking Groups’ Operational Efficiency - Ng, Chin Kong (2013)
Merger and acquisition activities of Malaysian financial institutions commenced in the mid-1980;necessitated by the ongoing economic recession. Since then, each subsequent economic crisis;namely the 1997 East Asian financial crisis and the more recent 2007 global financial crisis have provided further impetus for the financial industry to consolidate. It is the purpose of this paper to look at the relative efficiencies of each banks in 2007 (7 years after consolidation) and the market valuation of each bank vis-à-vis its efficiency score. The study is repeated in 2010 and any growth during the interim period is analyzed. Market valuations vis-à-vis each bank’s efficiency score is again observed. The different mechanics of mergers, the circumstances surrounding the mergers and the share holding composition of the acquirer and the target banks all plays a role in a banks operational efficiency. A market-based method using comparable (Tobin’Q ratio) is utilized in this case to provide the external market valuations of the specific bank, whereas the efficiency score of the bank operations is analyzed using input-oriented data envelopment analysis (DEA) using CAMELS variables as the input into the model.